Attention Deficit Hyperactivity Disorder (ADHD) in adolescence - Selleti, Maria Cláudia Silva Jardim (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
This research covers a current and extremely relevant topic when it comes to ADHD in adolescence. This study sought to delve deeper into the topic by investigating the characteristics of ADHD and the behavior of individuals with this disorder, in addition to understanding the diagnosis and treatment. For this, the methodology used was a literary review, studying authors such as Desidério and Miyazaki (2007), Gomes (2018), Pires et al. (2024), Braun et al. (2019) and Lima (2023). This research states that ADHD symptoms need to manifest in the individual between 6 and 12 years of age and that it is characterized by symptoms such as hyperactivity, inattention and impulsivity, and these symptoms sometimes lead the patient to unwanted impacts, such as isolation, excessive talking, dropping out of school and use of alcohol and other drugs. In addition to the challenges of diagnosis and treatment, it was also seen that families and schools must combine medication strategies and psychosocial treatments, in addition to developing a study routine and practicing physical exercises in order to alleviate symptoms.